Development of Phenomenon-Based Science Courses for Elementary Education Majors - Canipe, Martha (Innovations in Science Teacher Education, 2025)
This article describes the development and pilot implementation of a two-semester phenomenon-based science course sequence for elementary education majors. The courses were designed to address challenges related to elementary teachers' science content knowledge and to provide opportunities for science learning that intertwine core ideas, practices, and crosscutting concepts. Drawing on the principles of Ambitious Science Teaching, the courses were made up of units focused on an anchoring phenomenon. Student perceptions of the courses gathered through interviews indicated that the courses had a positive impact on how they viewed the process of learning science. Students highlighted the course's focus on the process of learning, the depth of investigation, and the collaborative nature of the learning experience. The article concludes with recommendations for science teacher educators interested in implementing similar courses or course units.